Gendering Talk - Hopper, Katherine (University of Michigan Press, 2023)
Men and women are not from separate planets. Making an original and significant argument, Gendering Talk puts gendered communication in perspective by showing that the problem with male/female communication is not how men and women talk to each other, but in how they listen. By closely examining the details of actual conversations between women and men—particularly the conversations of people “coupling”—Hopper draws on theories of arousal, relationship development, and play to trace the ways in which romantic couplings begin. Gendering Talk provides an engaging, highly entertaining, and far-reaching analysis of the ways in which people actively gender their talk, each other, and the social world. From the children’s game “Farmer in the Dell” to excerpts from classic and modern literature, and the media Hopper convincingly argues that talk between women and men is more alike than different.